The comedy of terrors: ideology and comedy in Marlowe's Doctor Faustus. Issue 1 (2nd January 2017) - Ladegaard, Jakob
ABSTRACT: While much recent scholarship asserts that the dark humor of Christopher Marlowe's The Jew of Malta (1589–1591) has a critical function, the political meaning of the comic elements of Doctor Faustus (1588–1593) has been largely ignored. This article aims to explore the critical function of comedy in the A-text of Doctor Faustus . The article does not mainly focus on the farcical scenes of the play, but argues that comedy pervades many parts – particularly the beginning – that have traditionally been read as 'serious' and even tragic. Inspired by Alenka Zupančič's philosophical work on comedy, The Odd One In (2008), it is further argued that this comic undercurrent alters our perception of the protagonist and his bargain with Mephistopheles from elements in a metaphysical drama to figures in a critical exploration of the material life of ideas – especially the official religious and political doctrines of the Elizabethan state. Seen from the perspective of comedy, Doctor Faustus thus invites its early modern audience to reflect on the paradoxes of ideology as a both real and illusory mediator between state power and the subject.